Who is more anxious in learning a foreign language: males or females? - Defira Afrianti; Mauloeddin Afna (INSPIRA: Indonesian Journal of Psychological Research, 2020)
This study aims to investigate English speaking anxiety experienced by students on gender difference. This quantitative study applied a comparative design with 122 English students (male: 20,5%) as a research sample using the proportionate stratified random sampling technique. The data were collected by Foreign Language Classroom Anxiety Scale by Horwitz that consist of 33 statements. By independent sample t-test, the result showed that the anxiety means a score of male students was 89,60, and the female was 93,24, with a p-value of 0,203. It indicated that the anxiety experienced by males and females was not significantly different.